Real-world pharmacovigilance insights into drug-induced risk of alopecia - Li, Huixiang; Wei, Haijian; Shentu, Qiaoqiao; Cui, Jianxin; Chen, Jiaojiao (Frontiers in Pharmacology, 2025)
BackgroundAlopecia is a significant adverse effect that profoundly impacts quality of life. Although numerous medications are implicated, the real-world risk profiles across drug classes and patient demographics remain poorly quantified.ObjectiveTo identify and characterize drugs associated with alopecia using real-world data from the FDA Adverse Event Reporting System (FAERS).MethodsFAERS reports from Q1 2004 to Q4 2024 were analyzed using four disproportionality methods (ROR, PRR, BCPNN, MGPS) to detect signals of drug-alopecia associations. Subgroup analyses were conducted by age, gender, and drug category. Time-to-onset (TTO) was analyzed using the Weibull distribution model.ResultsA total of 181,838 reports with drug-associated alopecia were identified. The mean age was 53.84 ± 16.28 years, and 76.82% of reports were from females. Oncology medications showed strongest association (37.5%), especially docetaxel (ROR = 70.38). Endocrine (18.8%) and immune system medications (10.9%) were also prominent. The TTO analysis revealed a bimodal distribution, with 40.2% of cases occurring within 30 days and 13.1% manifesting at 240–360 days. Males experienced a significantly shorter onset latency compared to females (108 days vs. 236 days, P < 0.001). Oncology drugs also showed shorter latency than non-oncology agents (198 vs. 308 days, P < 0.001). Notably, comparison with United States prescribing information revealed that 23.4% of high-signal drugs lacked documentation of alopecia in their official labels.ConclusionThis large-scale pharmacovigilance study identified 64 drugs with significant alopecia signals, highlighting distinct demographic patterns and latency periods. The findings underscore the need for heightened clinical vigilance, gender-specific monitoring, and updates to labels to better reflect real-world risks.